Old boys - Mccarry ,charles; Blake, Edward, narrator (new york : the overlook press, 2004)
Paul Christopher, discouraged by the world of espionage, must find a "mole" and demand justice from enemies, past and present. His trail leads to the horrors of the Nazi era, and to the post-Vietnam period. * Strong language and descriptions of sex *.
Reissue of: Washington, DC : Library of Congress, 1990. (New York : AFB).
Text originally published: New York : New American Library, 1983.
Narrator: Edward Blake.
All Ages.
Keywords: Spy stories